Mesh Sequence Morphing. (24th August 2015) - Chen, Xue; Feng, Jieqing; Bechmann, Dominique
Abstract : Morphing is an important technique for the generation of special effects in computer animation. However, an analogous technique has not yet been applied to the increasingly prevalent animation representation, i.e. 3D mesh sequences. In this paper, a technique for morphing between two mesh sequences is proposed to simultaneously blend motions and interpolate shapes. Based on all possible combinations of the motions and geometries, a universal framework is proposed to recreate various plausible mesh sequences. To enable a universal framework, we design a skeleton‐driven cage‐based deformation transfer scheme which can account for motion blending and geometry interpolation. Abstract: Morphing is an important technique for the generation of special effects in computer animation. However, an analogous technique has not yet been applied to the increasingly prevalent animation representation, i.e. 3D mesh sequences. In this paper, a technique for morphing between two mesh sequences is proposed to simultaneously blend motions and interpolate shapes. Based on all possible combinations of the motions and geometries, a universal framework is proposed to recreate various plausible mesh sequences. To enable a universal framework, we design a skeleton‐driven cage‐based deformation transfer scheme which can account for motion blending and geometry interpolation. To establish one‐to‐one correspondence for interpolating between two mesh sequences, a hybrid cross‐parameterization scheme that fully utilizes the skeleton‐driven cage control structure and adapts user‐specified joint‐like markers, is introduced. The experimental results demonstrate that the framework, not only accomplishes mesh sequence morphing, but also is suitable for a wide range of applications such as deformation transfer, motion blending or transition and dynamic shape interpolation.